Degradation of imipramine by vacuum ultraviolet (VUV) system: Influencing parameters, mechanisms, and variation of acute toxicity. (October 2019) - Xie, Pengchao; Zou, Yujia; Jiang, Shan; Wang, Jingwen; Zhang, Li; Wang, Zongping; Yue, Siyang; Feng, Xiaonan
Abstract: Degradation of imipramine (IMI) in the VUV system (VUV185  + UV254 ) was firstly evaluated in this study. Both HO oxidation and UV254 direct photolysis accounted for IMI degradation. The quantum yields of UV254 direct photolysis of deprotonated and protonated IMI were 1.31 × 10 − 2 and 3.31 × 10 − 3, respectively, resulting in the higher degradation efficiency of IMI at basic condition. Increasing the initial IMI concentration lowered the degradation efficiency of IMI. While elevating reaction temperature significantly improved IMI degradation efficiency through the promotion of both the quantum yields of HO and the UV254 direct photolysis rate. The apparent activation energy was calculated to be about 26.6 kJ mol −1 . Negative-linear relationships between the k obs of IMI degradation and the concentrations of HCO3 − /CO3 2−, NOM and Cl − were obtained. The degradation pathways were proposed that cleavage of side chain and hydroxylation of iminodibenzyl and methyl groups were considered as the initial steps for IMI degradation in the VUV system. Although some high toxic intermediate products would be produced, they can be further transformed to other lower toxic products. The good degradation efficiency of IMI under realistic water matrices further suggests that the VUV system would be a good method to degrade IMI in aquatic environment. Graphical abstract: Image 1 Highlights: The degradation of imipramine (IMI) in the VUV system was firstly studied. Both HO. oxidation and UV254 direct photolysis contributed to IMI degradation. Direct photolysis of deprotonated IMI contains higher quantum yield than protonated IMI. The pathways of IMI degradation in the VUV system were proposed. The variation of acute toxicity during IMI degradation was evaluated.